Impaired Very‐Low‐Density Lipoprotein catabolism links hypoglycemia to hypertriglyceridemia in Glycogen Storage Disease type Ia. Issue 4 (7th April 2021) - Hoogerland, Joanne A.; Peeks, Fabian; Hijmans, Brenda S.; Wolters, Justina C.; Kooijman, Sander; Bos, Trijnie; Bleeker, Aycha; van Dijk, Theo H.; Wolters, Henk; Gerding, Albert; van Eunen, Karen; Havinga, Rick; et al.
Abstract: Prevention of hypertriglyceridemia is one of the biomedical targets in Glycogen Storage Disease type Ia (GSD Ia) patients, yet it is unclear how hypoglycemia links to plasma triglyceride (TG) levels. We analyzed whole‐body TG metabolism in normoglycemic (fed) and hypoglycemic (fasted) hepatocyte‐specific glucose‐6‐phosphatase deficient (L‐ G6pc −/− ) mice. De novo fatty acid synthesis contributed substantially to hepatic TG accumulation in normoglycemic L‐ G6pc −/− mice. In hypoglycemic conditions, enhanced adipose tissue lipolysis was the main driver of liver steatosis, supported by elevated free fatty acid concentrations in GSD Ia mice and GSD Ia patients. Plasma very‐low‐density lipoprotein (VLDL) levels were increased in GSD Ia patients and in normoglycemic L‐ G6pc −/− mice, and further elevated in hypoglycemic L‐ G6pc −/− mice. VLDL‐TG secretion rates were doubled in normo‐ and hypoglycemic L‐ G6pc −/− mice, while VLDL‐TG catabolism was selectively inhibited in hypoglycemic L‐ G6pc −/− mice. In conclusion, fasting‐induced hypoglycemia in L‐ G6pc −/− mice promotes adipose tissue lipolysis and arrests VLDL catabolism. This mechanism likely contributes to aggravated liver steatosis and dyslipidemia in GSD Ia patients with poor glycemic control and may explain clinical heterogeneity in hypertriglyceridemia between GSD Ia patients. Abstract :